SEISMO-TECTONIC AND GEODYNAMIC FEATURES DAGESTAN SECTOR OF THE EASTERN CAUCASUS - R. A. Magomedov; S. A. Mamaev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In the analysis of stock and published geological and geophysical material made a new generalized fault-block tectonics of the region, which the service provides the necessary basis for studying the processes of interaction blocks, localization of sources of stress, the study of the movements along block boundaries and has periostattion is to identify potential seismic foci, long-term forecast of their next activation and adequate assessment of seismic hazard and seismic risk in this densely populated and industrialized region of the country.